Parochial Neo-Colonialism and the Perpetuation of Refugee Marginalization: A Postcolonial View of European Immigration in “The Lightless Sky” (Journal of Asian Development Studies, 2025)
This research paper examines Parochial Neo-Colonialism and its role in perpetuating refugee marginalization through a postcolonial theoretical framework, focusing on European immigration policies as represented in Gulwali Passarlay’s memoir, The Lightless Sky. The analysis investigates how myopic, exclusionary attitudes towards immigration encapsulate a neo-colonial paradigm, wherein former colonial powers sustain indirect hegemony over less developed nations through mechanisms of economic exploitation, political influence, and cultural imposition. This study employs a critical lens to assess how such parochial perspectives and neo-colonial practices systematically reinforce the marginalization and dehumanization of refugees, thereby perpetuating structural inequalities rooted in colonial histories. By engaging with Passarlay’s autobiographical account, the paper highlights how contemporary European immigration policies and societal attitudes reflect and institutionalize the exclusion of refugees, elucidating the persistence of colonial legacies in modern migration regimes. The objective is to comprehensively analyse how these neo-colonial dynamics and parochial biases shape the refugee experience, contributing to ongoing scholarly discourse on the intersections of colonialism, migration, and global inequality.